[18F]Fluoride PET Indicates Reduced Bone Formation in Severe Glucocorticoid-induced Osteoporosis - Berding, G.; Kirchhoff, T. D.; Burchert, W.; Hoff, J. v. d.; Zeidler, H.; Hundeshagen, H.; Knapp, W. H. (Nuklearmedizin - NuclearMedicine, 1998)
A 61-year-old female patient presenting with mixed connective tissue disease (Sharp syndrome), underwent a long-term high dose glucocorticoid treatment because of multiple organ manifestations. Under steroid therapy she developed severe osteoporosis resulting in multiple fractures. A dynamic [18F]fluoride PET study in this patient revealed reduced fluoride influx in non-fractured vertebrae. This finding corresponds to pathogenetic concepts which propose an inhibition of bone formation as major cause of glucocorticoid-induced osteoporosis. In the light of the presented case it seems to be promising to evaluate the diagnostic benefit of [18F]fluoride PET in osteoporosis.
Keywords: Osteoporosis; glucocorticoids; [18F]fluoride ion; positron emission tomography (PET)